Sodium selenite promotes osteoblast differentiation via the WNT/β-catenin signaling pathway - Ashish Ranjan Sharma; Garima Sharma; Yeon-Hee Lee; Chiranjib Chakraborty; Sang-Soo Lee; Eun-Min Seo (Cell Journal, 2022)
Objective: Osteoporosis is regarded as a silent disorder affecting bone slowly, leading to an increased risk of fractures. Lately, selenium has been found to be associated with the acquisition and maintenance of bone health by affecting the bone remodeling process. However, the mechanism of action of selenium on bone is poorly understood. Here, the protective effects of sodium selenite on the differentiation process of osteoblasts as well as under oxidative stress-induced conditions were evaluated.Materials and Methods: MC3T3-E1 cells, were treated with a various doses (0, 0.1, 0.2, 0.4, 0.8, 1.6, 3.2, 6.4 ug/ml) of sodium selenite. Cell viability and cytotoxicity were observed by MTT and LDH assay. The osteogenic activity and expression level of osteogenic markers were confirmed through ALP activity, real-time RT-PCR and sirius red staining. Role of sodium selenite and involvement of WNT signaling was assessed by Axin-2 reporter assay and western blotting.Results: It was observed that the sodium selenite could promote the ALP activity and collagen synthesis in pre-osteoblasts. Moreover, sodium selenite increased the mRNA expression levels of osteogenic transcriptional factors, such as runt-related transcription factor 2 (Runx2) and osterix (OSX). In addition, the terminal differentiation markers, such as osteocalcin (OCN), and collagen 1α (Col1α), were also increased. Treatment of sodium selenite recused the H2O2-induced inhibition of osteoblastic differentiation of pre-osteoblasts cells. Furthermore, sodium selenite restored the H2O2 repressed β-catenin stability and axin-2 reporter activity in MC3T3-E1 cells implicating involvement of WNT signaling pathway.Conclusion: It may be concluded that selenite can stimulate bone formation and rescue the oxidative repression of osteogenesis by activating WNT signaling pathway and may act as a potential therapeutic intervention for osteoporosis.